Facile and scalable preparation of gradient multilayer nanocomposite structure with preeminent microwave absorption and radar cross section reduction capability - Rajhi, Ali A. (Ceramics international, 2024)
The pressing need for the enhancement of stealth materials that are harmonious with state-of-the-art military equipment is critical, as it plays a pivotal role in bolstering the survivability and operational capabilities of advanced military technology. This research offers a straightforward approach for fabricating a gradient triple-layer absorber utilizing a Cu2O/h-BN nanocomposite and FeCoNi magnetic compounds, characterized by reduced thickness, designed for X-band wave spectrum attenuation purposes. The primary objective of this study is to examine the electromagnetic wave absorption characteristics of single-layer samples and subsequently develop a triple-layer gradient sample with distinct electromagnetic wave stealth features based on the findings. Optimal performance was observed in the gradient sample, where Cu2O/h-BN nanocomposite with 20 and 10 wt% was incorporated as a matching layer with thicknesses of 0.5 and 0.5 mm, respectively, and FeCoNi with 20 wt% was employed as an absorbing layer with a 0.4 mm thickness, surpassing the performance of the other samples. The optimal sample achieves a dissipation loss of −45.6 dB and a bandwidth of 2.9 GHz, all while maintaining a total thickness of just 1.4 mm. Facilitating multiple heterogeneous interfaces among layers, substances, and the synergistic interaction between constituent elements and layers’ thickness and arrangement enable this gradient configuration to demonstrate exceptional performance in radar stealth compatibility.